FORMATION OF SAFETY SKILLS OF STUDENTS OF MACHINE-BUILDING SPECIALTIES: THEORETICAL ASPECT - Sofia Dembitskaya (Borys Grinchenko Kyiv Metropolitan University, 2019)
The necessity of development of skills of safety activity of students of machine-building specialties in the process of professional training in institutions of higher education of technical direction are considered in the article. The urgency of the problem of formation of skills of safety activity future specialists in mechanical engineering in the process of professional training in institutions of higher education of technical direction is determined by the peculiarities of future professional activity. The key concepts of research are analyzed, in particular such as «safety activity», «safety competence», «culture of safety» and actual ways of developing labour-protection competence in the process of training specialists in machinebuilding specialties. Based on a solid analysis of scientific publications on the research problem, we outlined the conditions for the formation of skills of labour protection activities of future specialists in mechanical engineering in institutions of higher education. We relate to them clarification of the content of the concept of «labour protection competence» taking into account the peculiarities of the professional activity of specialists in the machine-building industry, determination of the components of safety competence of specialists of the machine-building industry and its interconnections in the structure of professional competence, determination of peculiarities and tasks of formation of safety competence of specialists in the machinebuilding industry in the system of professional training, ensuring motivation for the development of safety competence of future specialists in the machine-building industry as a necessary condition for professional adaptation and further professional growth, determination of the peculiarities of skills development in safety activities in the process of theoretical and practical training, industrial practice and graduation design, as well as the selection of appropriate pedagogical means for the educational process. Prospects for further research, we see in the development of methodological conditions and ways of developing the safety competence of future specialists in mechanical engineering at all stages of professional training in higher education institutions